PENGARUH PROFITABILITAS DAN PERBEDAAN OPINI INVESTOR TERHADAP KINERJA HARGA SAHAM - Eka Damayanthi, I Gusti Ayu; Aryani Merkusiwati, Ni Ketut Lely; Lola Ulianti, Ni Putu; Candra Kusuma, I Gede; Wistika Putra, Agus Erik (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This research aims to empirically test the influence of profitability and differences in investor opinion on share price performance in banking companies. The research phenomenon explains that at the start of the Covid-19 pandemic, the banking sector experienced a decline in share price performance because investors were suspected of having concerns about investing in the risky banking sector due to the pandemic. The research wants to prove whether profitability factors and differences of opinion during the pandemic influence stock price performance. The research sample was 40 banking companies registered on the IDX in 2020. The method used is multiple linear regression analysis. The results of this research show that an increasing profitability value will be followed by an increase in company stock returns. This shows that profitability has a direct relationship with stock returns. The research results also show that high differences in investor opinion reduce stock price performance, and low differences in investor opinion will increase stock price performance. The results of this research support the signal theory.